2010
DOI: 10.1167/iovs.09-4090
|View full text |Cite
|
Sign up to set email alerts
|

Eyelid Pressure and Contact with the Ocular Surface

Abstract: Purpose. To investigate static upper eyelid pressure and contact with the ocular surface in a group of young adult subjects. Methods. Static upper eyelid pressure was measured for 11 subjects using a piezoresistive pressure sensor attached to a rigid contact lens. Measures of eyelid pressure were derived from an active pressure cell (1.14-mm square) beneath the central upper eyelid margin. To investigate the contact region between the upper eyelid and the ocular surface, the authors used pressure-sensitive pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 25 publications
2
61
0
Order By: Relevance
“…4,18 (4) A functional clinical study suggested that a zone in the width of about 600 mm, which would be within the range of the width of the lid wiper 5,10,15 (Knop et al 2007, Abstract at the TFOS 2007 Conference), is the contact zone of the eyelid border with the globe. 21 However, a previous study by the same group had reported some evidence that the line of Marx of about 100-mm width was the primary site of contact with the globe. 22 This assumption of the line of Marx being the wiping zone was also shared by other authors.…”
Section: Discussionmentioning
confidence: 95%
“…4,18 (4) A functional clinical study suggested that a zone in the width of about 600 mm, which would be within the range of the width of the lid wiper 5,10,15 (Knop et al 2007, Abstract at the TFOS 2007 Conference), is the contact zone of the eyelid border with the globe. 21 However, a previous study by the same group had reported some evidence that the line of Marx of about 100-mm width was the primary site of contact with the globe. 22 This assumption of the line of Marx being the wiping zone was also shared by other authors.…”
Section: Discussionmentioning
confidence: 95%
“…33 Alternatively, the lens may prevent frictional contact between the lid and the cornea during the blink, which can also stimulate nociceptors. 34,35 Lastly, microscopic epithelial defects may heal faster due to the bandage effect. 36…”
Section: Discussionmentioning
confidence: 99%
“…First, the upper eyelid might generate greater pressure on the superior cornea than the inferior cornea. [23][24][25] This could produce less edema or even a thinning of the epithelium at the superior midperiphery. Second, although the fitting of the OK lens was acceptable in the clinic and the visual acuity was satisfactory to all subjects, superior decentration of the lens might have occurred in most of our subjects.…”
Section: Discussionmentioning
confidence: 99%